2018
DOI: 10.1089/chi.2017.0269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Exercise on Adiponectin, Leptin, and Inflammatory Markers in Childhood Obesity: Systematic Review and Meta-Analysis

Abstract: Background: New findings on adipose tissue physiology and obesity-associated inflammation status suggest that modification of the adipokine level can be relevant for the long-term prevention of obesity-associated chronic disease.Objectives: The scope of the present study was to investigate the effectiveness of physical exercise in reducing the systemic inflammation related to obesity in children.Methods: We conducted a systematic review with meta-analysis of controlled randomized trials, identified through ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 54 publications
6
88
3
3
Order By: Relevance
“…Obesity is associated with lowered adiponectin, and increasing as well as decreasing levels of adiponectin have been found in pediatric intervention studies (68). Physical exercise alone was found sufficient to reduce leptin and raise adiponectin levels (68). Thus, the observed effects on adipokines in our study are in line with reports from other programs and indicate an effect of the intervention on the adipose tissue and associated metaflammation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Obesity is associated with lowered adiponectin, and increasing as well as decreasing levels of adiponectin have been found in pediatric intervention studies (68). Physical exercise alone was found sufficient to reduce leptin and raise adiponectin levels (68). Thus, the observed effects on adipokines in our study are in line with reports from other programs and indicate an effect of the intervention on the adipose tissue and associated metaflammation.…”
Section: Discussionsupporting
confidence: 90%
“…The metabolic change of adipokine expression in fat tissue induced by the intervention might play a significant role in the decline of IR. Obesity is associated with lowered adiponectin, and increasing as well as decreasing levels of adiponectin have been found in pediatric intervention studies (68). Physical exercise alone was found sufficient to reduce leptin and raise adiponectin levels (68).…”
Section: Discussionmentioning
confidence: 99%
“…Their use among athletes is very popular: most studies reported that over half of the athletes use supplements and food supplement use was more common among university students (in particular, those in health professional graduate courses) than high school students. Other studies reported even that 88% of the athletes use one or more nutritional supplements (Biffi et al, 2018;Sirico et al, 2018 a). A large range of different types and brands of products for nutritional supplementation (are present in the form of pills, tablets, capsules and liquids) is now really widespread and accepted by athletes (Mazzeo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Excess weight has an inflammatory effect (García-Hermoso et al, 2016). However, exercise can reduce the systemic inflammation associated with obesity (Sirico et al, 2018). The complications of obesity are due to metabolic disorder induced by an excessive accumulation of fat, which leads to cardiovascular disease (CVD) and type 2 diabetes mellitus (Morandi and Maffeis, 2014).…”
Section: Introductionmentioning
confidence: 99%